Kedudukan Saksi Non Muslim dalam Perkawinan Menurut Peraturan Perundang-Undangan di Indonesia - Atus Ludin Mubarok (Mutawasith: Jurnal Hukum Islam, 2021)
In the field, it often happens that a Muslim marries a convert to a Muslim woman with a large non-Muslim family status. In marriage, converts submit non-Muslim witnesses. What is the status of their testimony according to the law. The purpose of this study was to determine the position of non-Muslim witnesses to marriage according to the legislation with a qualitative method, a literature study approach. Source of data in the form of legislation related to family law. It is done by deductive-inductive method. From the discussion, it can be concluded that the Indonesian laws and regulations stipulate that marriage witnesses must be Muslim. A non-Muslim is not accepted as a witness to a marriage. In the case of divorce and reconciliation, the witness's special religious requirements are set. There is an opportunity for non-Muslims to be witnesses in ruj'u and divorce cases. Divorce on the grounds of shiqaq must be heard from witnesses who come from the husband and wife's family. That is, Article 76 of Law no. 7/1989 paragraph (1) still applies to family and close people of husband and wife who are non-Muslims and must provide testimony as witnesses.